Pemenuhan Sarana Prasarana yang Aksesibel Bagi Penyandang Disabilitas di Pengadilan Negeri se Daerah Istimewa Yogyakarta - Muhammad Mega Firstian Utama; M. Syafi’ie (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
Efforts to guarantee equal rights for disabilited people through the fulfillment of accessible facilities and infrastructures in district courts to support the establishment of justice that inclusive of people with disabilities. Regulations that accommodate efforts to fulfill accessible facilities and infrastructure for peoples with disabilities. In the real case, it turns out that there are still many people with disabilities who didnt received accessible facilities and infrastructure according to their needs when they are going to visit the court. Therefore, the purpose of this research is to identify and analyze the fulfillment of accessible facilities and infrastructure and obstacles are encountered in efforts to realize accessibility to district courts throughout DIY based on the applicable normative provisions. This research is an empirical legal research using analytical methods obtained from the field associated with secondary data. Based on the research that has been conducted, it is found that majority district courts in DIY didnt fully accommodated the provision of accessible facilities and infrastructure, for persons with disabilities. Several obstacles were found in realizing accessible facilities and infrastructure for people with disabilities due to the absence of technical guidelines regarding the standardization of accessible facilities and infrastructure for persons with disabilities and the limited availability of the budget, that will be issued to realize this fulfillment. Therefore, to realize the fulfillment of accessible facilities and infrastructure, it is necessary to qualify internal policies from the courts and government.